Innovative Photovoltaic Cooling System - Ryan Bugeja; Luciano Mule’ Stagno (Invention Disclosure)
With the ever-increasing adoption of solar energy and the lack of space for PV installations, targeting maximum photovoltaic operational efficiencies has become essential. One of the key challenges faced by PV installations in warm climates is thermal management, which is caused by increasing temperatures due to PV conversion inefficiencies and limited ventilation possibilities in certain installations. Despite prior art, further improvement is still needed to provide a novel system that can offer more efficient and controllable temperature decrease of photovoltaic modules in both land and offshore installations. The present invention, termed IPCoSy, satisfies the aforementioned needs in the art by providing a novel system for cooling a solar panel assembly, including at least one photovoltaic module having a plurality of solar cells generating electrical power and a PV junction box attached to the back of the photovoltaic module. A part of this invention discloses a new type of PV module that is a modification of standard commercial modules. This new PV module incorporates a water chamber at the back of a solar cell assembly to regulate operational temperatures. Another part of this invention presents an after-market cooling system that can be fitted to existing standard PV modules to add the cooling effect. This part of the invention presents solid and flexible water tanks that can be fitted directly into a gap at the back of standard PV modules. Moreover, this invention presents details on parts that distinguish this cooling system from prior art, such as an internal stream spreader to obtain better fluid dynamics and external fittings that allow the PV module to be installed at any tilt angle without jeopardizing the cooling effect. Finally, this invention discloses different application areas of this cooling system, such as residential and industrial water heating, reverse osmosis plants and offshore photovoltaic installations, showcasing the product's versatility, adaptability and large market suitability.